Financial Drivers of Tax Aggressiveness: The Impact of Deferred Tax Assets, Liquidity, and Capital Intensity - Afifah, Nur; Madjid, Suhirman (Santoso Academy Network, 2025)
This study examines the influence of deferred tax assets, liquidity, capital intensity, and return on assets on tax aggressiveness in coal mining companies listed on the Indonesia Stock Exchange during 2017–2021. Using a quantitative approach, secondary data from corporate financial statements were analyzed through multiple linear regression. The study contributes by highlighting how financial characteristics specific to the extractive sector shape corporate tax behavior. The results show that deferred tax assets do not significantly affect tax aggressiveness, while liquidity, capital intensity, and return on assets have a significant influence. These findings suggest that firms with stronger short-term financial capacity, greater fixed asset investment, and more efficient asset utilization have increased flexibility in managing tax obligations. From a managerial perspective, the study emphasizes the importance of aligning tax planning with liquidity management and investment decisions to achieve fiscal efficiency within regulatory limits. The study also provides policy implications for regulators by underscoring the need for stronger oversight of firms with high liquidity and capital intensity, as these characteristics create greater opportunities for tax aggressiveness. Finally, future research may incorporate corporate governance and ownership structures to further explain variations in tax-aggressive behavior across industries